Home Visit Program in Minimizing Stay in Class and Dropout at Elementary School of Sampangan, Semarang - Ibda, Hamidulloh; Wijayanti, Dian Marta (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2020)
This study describes the home visit program in minimizing the total of children stay in class and dropout at Elementary School, Semarang City. This study uses action research methods that use the model design of Kemmis and Mc. Taggart whose devices consist of planning, action, observation, and reflection. Data collection techniques in this study used interviews and observation. Based on the results of the study, there are significant data on reducing the level of stay in class and dropout in Elementary School of Sampangan 01. In the 2017-2018 school year, there were 11 children stay in class and 4 children who dropout. In the school year 2018-2019 Because the total of children stay in class has been dropped to 6 and dropped out of school 0. From these results obtained significant results from the home visit program in reducing the dropout rate in children.